Initial investigations and clinical outcome in COVID-19 patients - Shrivas, Vijay K.; Rai, Manoj K.; Chandel, Sandhya (International Journal of Advances in Medicine, 2022)
Background: Coronavirus disease 2019 (COVID-19) has significant impact on the health infrastructure all over the world including India. We wanted to see whether the routine initial investigations done in COVID 19 patients reflect the prognosis and outcome of the patient. Methods: It is a retrospective study involving the confirmed covid 19 patients admitted between April 2021 to May 2021. The initial investigations done at the time of admission were studied in relation to outcome of the patient in the form of survival or death of the patient. Results: A total of 364 patients were studied. 295 (81.05%) patients survived and 69 (18.96%) patients died. Highest mortality was observed in 60% of patients with hemoglobin below 7.0 mg/dl, 40.00% of patients with platelet count below 50000/cml, 28.80% with neutrophil lymphocyte ratio more than 5.5, 32.81% with CRP more than 100 mg/L, 100% with D dimer more than 5000 ng/ml, 33.33% with Ferritin more than 1500 ng/ml, 29.54% with IL-6 more than 100 pg/ml, 23.14% with Random blood sugar more than 200 mg/dl, 37.50% with creatinine more than 2.0 mg/dl, 75% with Bilirubin more than 2.0 mg/dl, 42.85% with SGOT more than 201 mg/dl, 22.22% with SGPT more than 201 mg/dl, 38.46% with serum Procalcitonin more than 2.0 mg/dl. CT Chest severity score of 21 to 30 and 31 to 40 lead to mortality of 19.51% and 40.00% respectively. Conclusions: The physician who is taking care of COVID-19 patients must get extra cautious regarding prognosis if he gets above initial parameters deranged in isolation or combination.